A DISCOURSE ANALYSIS OF INTERNATIONAL LEADERS AND GLOBAL MEDIA NARRATIVES: BUILDING ANTI-ISLAM STEREOTYPES - Areeba Riaz; Ayesha Noor; Dr Muhammad Wasim; Saman Hassan (International Journal of Contemporary Issues in Social Sciences, 2024)
Islamophobia is not a novel phenomenon. It has been throughout history from the times of Prophet Muhammad (PBHU) and his caliphates to the crusade wars to the recent examples of Turk-Muslim assimilation in 1989 and mass killings of Bosnian Muslims in 1995. But it has seen enormously raised after the attacks of September 11, 2001. This research is a qualitative study of the discourse and acts of Western Media and Internationally influential leaders. The analyses the discourse of global Media and International leaders through the lens popular theories. It invokes Critical discourse analysis to find out the relationship between power and language and the use of spiteful language against Muslims by International leaders and Western Media. It also employs Orientalism to examine the creation of self vs others dichotomy. This research hunted some examples of stereotypical coverage of events in press and the remarks and discourses of Western leaders against Muslims. Discourse does not only imply the words or utterance but also the acts in the sense of Paul Gee’s ’small d discourse’ and ’capital d discourse’ Hence, the meaning of discourse here involves ideas, beliefs, behaviours and consequent actions as well. This research has also included a survey statistic to know public perception of Pakistani people on the questions related to subject matter of the research. The graphical results are included in the discussion of the research.